The impact of humic acid additives on mineral metabolism of rabbits in the postnatal period of ontogenesis - Rybalka, M. A.; Stepchenko, L. M.; Shuleshko, O. O.; Zhorina, L. V. (Regulatory Mechanisms in Biosystems, 2020)
Humic acids are characterized by chelating properties due to which they are able to influence the mineral metabolism in animals. Rabbits have species-specific characteristics of mineral metabolism, which distinguishes them from most species of mammals. For the experiment, 16 rabbits of 45-day-old of Hyplus breed were divided into the experimental and control group of 8 rabbits in each. The animals were 15 days in the preparatory period. The rabbits of the experimental group received humic acid additive individually with water in the amount of 5 mg/kg, the rabbits of the control group received pure water in the same amount. The ability of humic acid additive to increase the content of calcium, ionized calcium, iron, to correct the content of copper and zinc, and also to increase the activity of alkaline phosphatase in the blood serum of rabbits of the experimental group has been proved. We observed the early effect of the humic acid additive on increasing the content of iron and calcium ionized and a later effect on the activity of alkaline phosphatase and an increase in the content of copper in the blood serum. The influence of humic acid additive on the distribution of calcium, phosphorus, manganese, copper and zinc in bone tissue is determined. According to a histological study, there was a significant increase in the number of layers of osteons and osteoblasts in the bone tissue of the femur, an increase in the number of osteons and osteoblasts in the bone tissue of the sternum and an increase in the number of columns of chondrocytes and an increase in the number of chondrocytes in the column in the cartilaginous tissue of the sternum. The results of a histological study of bone tissue, together with an increase in structural macroelements in it and redistribution of osteotropic trace elements in the blood and bone tissue suggest the possibility of using a humic acid additive to intensify the growth and mineralization of bone tissue, which can improve the state of bone tissue of rabbits in the postnatal period ontogenesis.